Equivalência de estímulos e ensino de leitura: uma revisão sistemática da literatura - Silva, Graciane Barboza da (2018)
The present paper aimed to carry out a systematic review of the studies on the stimuli equivalence and reading teaching, between 2008 and 2017. This proposal supports the notion that studies on the stimuli equivalence are among the possibilities to address teaching inefficiency. Moreover, systematizing the produced knowledge in the area could develop an agenda for future research. Articles from CAPES and PEPSIC databases were analyzed and selected from previous studies, through a combined search of stimulus equivalence descriptors and reading. A total of twenty articles were included and submitted to the Checklist Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) in order to classify the quality level of the description of the studies. The articles were also submitted to categories analysis to identify their bibliometric properties, objectives, design characteristics and results. It was identified that studies on the equivalence of stimuli continue, for the most part, developed and published in postgraduate/periodical programs in the areas of Psychology and/or Behavior Analysis. Production trends are more frequent in the Midwest, especially in universities of São Paulo (USP, UFSCar, UNESP, PUC); North, highlighting the state of Pará (UFPA); South, highlighting the state of Paraná (UEL). Most of the studies aimed at evaluating teaching procedures based on the stimulus equivalence paradigm on target performance. It was observed that the school is the place where most studies were carried out, mostly with children of typical development, not readers, from the age group of six to seven years predominantly, and with three participants mainly. Regarding the teaching units, it was identified that the word continues to be the main unit of teaching and generalization, and also, even in a lesser extent, the use of sentences and texts. The compilation of the main findings shows that there are consistent and promising empirical data regarding naming performances, oral reading/textual behavior, reading comprehension, recombination, sentences/clauses reading, reading in individuals with atypical development and teaching procedures based on the stimulus equivalence in a collective situation. Nonetheless, a review of the procedure step, in order to guarantee a better experimental and methodology control, including variables that show potential for an effective teaching technology, the development of research that approaches the reality of the classroom and the need to replicate the study in subjects with repertoire variability are necessary. The STROBE checklist adaptation for quality analysis of the studies, metaanalysis, peer evaluation, and search expansion in other national and international databases are suggestions for future systematic review studies.